Major Sickle Cell Disease in Pregnant Women at University Teaching Hospital of Cocody in Cote d'Ivoire, a Low Resources Country - Dehi Boston Mian; Virginie Aya Angoi; Christiane Jivir Nsahlai; Joachim Konan; Kinifo Hamadou Yeo; Koffi N'Guessan; Serge Boni (IMR Press, 2023)
Background: Sickle cell disease (SCD) is one of the most prevalent genetic disorders, including major SCD and SC Trait (SCT) genotypes. Many studies have shown a negative association between major SCD and pregnancy. However, they are underestimated in Cote d'Ivoire statistics. To provide consistent data on SCD in pregnancy, we compare outcomes between women with normal hemoglobin (Hb) genotype and major SCD. Methods: A retrospective, and case-control study in the University Hospital of Cocody, from 2015 to 2018, analyzed maternal and fetal outcomes, comparing the Cases Group: major SCD (HbSS, HbSC) and Control Group: normal hemoglobin (Hb) genotype A. Only pregnancies with gestations longer than 28 weeks were included. No cases of thalassemia or variant of hemoglobin were found. Local protocols recommended systematic use of vasodilators or analgesics, folic acid, and high concentrations of inhaled oxygen during labor, associated with fluid and/or blood transfusion. We excluded sickle cell trait (SCT) genotype AS (HbAS), and incomplete data. A logistic regression was exploited to gauge the risk factors. We used SPSS version 19 (IBM Corp., Armonk, NY, USA) for statistical analysis, and calculate the adjusted odds ratio and 95% confidence interval. Results: We registered 156 major SCD (0.92%), compared to 312 HbAA. In Cases Group 27.6% were multigravidas (>4), young aged (≤20) (16.0%), and well-educated (43.6%). Major SCD were HbSC (33.3%) and HbSS (66.7%). The commonest maternal antenatal complication in major SCD was anemia (p < 0.0001), vaso occlusive crisis (p < 0.0001), and pregnancy-induced hypertension (p < 0.0001). Blood transfusions were significant in the SCD group (p < 0.0001). No significant difference between the groups regarding stillbirths (p = 0.3150) was recorded. Moreover, a significant risk in the major SCD genotype was low birth weight (LBW) (p < 0.0001), negative Apgar in the 5th minute (p < 0.0001), vaso-occlusive crisis (VOC) (p < 0.0001), and acute chest syndrome (ACS) (p < 0.0019). Conclusions: The findings of the survey suggest better fetal and maternal prognosis in HbAA compared to major SCD. Multidisciplinary team management is necessary to improve those outcomes. Patient awareness and education, and early and effective prenatal care are useful to avoid those risks.